(untitled) (Global Journal of Human-Social Science, 2016)
In this paper I have briefly discussed whether should Carrefour expand into Vietnam or not. Hypermarkets market is growing, and Carrefour has built a very impressive brand name and has gone to great heights to become the world’s largest retailer. Vietnam also is a growing country, and could be good chance for Carrefour there. I used PEST analyses to find out the possibility of Carrefour expansion into Vietnam. I went through the political, economic, sociocultural, and technological factors. By the end of this paper, you will find the results and recommendations.